Union instability as an engine of fertility? A micro-simulation model for France - Elizabeth Thomson; Maria Winkler-Dworak; Martin Spielauer; Alexia Prskawetz (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2009)
Micro-level relationships between union formation or dissolution and childbearing have implications for fertility that have not been thoroughly examined. In this paper, we suggest that these relationships comprise an 'engine' that produces variation and change around replacement level fertility. On the one hand, union dissolution reduces opportunities for conceiving and bearing children. At the same time, it produces a pool of persons who may enter new partnerships and produce 'extra' children. The balance between these two opposing forces and their implications for fertility levels is unknown and will depend in part on the timing of union formation and parenthood. In this paper, we estimate the parameters of these micro-level relationships for female respondents to the 1999 French 'Etude de l'Histoire Familiale'. We use those parameters to simulate the implications of non-union childbearing, union dissolution and re-partnering for completed family size. We also investigate the extent to which links between union formation or dissolution and childbearing depend on the timing of unions and births.
Keywords: 300; Union instability; fertility; France; Nichteheliche Kinder; Sozialer Wandel; Fertilität; Frankreich